1993
DOI: 10.1002/ardp.19933260302
|View full text |Cite
|
Sign up to set email alerts
|

Saturable Enantioselective First‐pass Effect for Carvedilol after High Oral Racemate Doses in Rats

Abstract: Carvedilol shows a highly enantioselective first-pass extraction after therapeutic p.o. doses with preferential extraction of the S-enantiomer. To investigate, whether the enantioselective first-pass metabolism is saturable, male Sprague-Dawley rats were administered increasing single doses of R/S-carvedilol (p.o., 5-30 mg/kg; i.v., 5 and 10 mg/kg), and the individual stereopharmacokinetics were studied. Like in humans the plasma concentrations of R-carvedilol exceeded always those of S-carvedilol. As expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…When CAR was given orally, the elimination halflife (t 1/2 ) usually varied between 3.1 and 18 h [17,[33][34][35][36][37]. In this study, the t 1/2 was 3.2 h after administration of a 1.5-1.8 mg doses for each rat in non-compartment model analysis, which is in good agreement with the reported value.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When CAR was given orally, the elimination halflife (t 1/2 ) usually varied between 3.1 and 18 h [17,[33][34][35][36][37]. In this study, the t 1/2 was 3.2 h after administration of a 1.5-1.8 mg doses for each rat in non-compartment model analysis, which is in good agreement with the reported value.…”
Section: Discussionsupporting
confidence: 91%
“…There are few reports on carvedilol pharmacokinetic study in rats [17,[33][34][35][36][37]. When CAR was given orally, the elimination halflife (t 1/2 ) usually varied between 3.1 and 18 h [17,[33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 97%
“…The enantioselective pharmacokinetics of CARV has been widely investigated in rat, monkey, man and congestive heart failure (CHF) patients (Yang et al, 2004;Saito et al, 2006;Stahl et al, 1993;Fujimaki et al, 1990;Neugebauer et al, 1990). All results have led to the conclusion that (S)-enantiomer has greater intrinsic clearance in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Linear pharmacokinetics of carvedilol has been described in elderly subjects after oral administration of 25–50 mg of the drug [31] . Conversely, a saturable first‐pass effect for carvedilol was found in rats after high oral racemate dosing [32] . Our results suggested that, after application of a single intravenous dose over the range of 1–5 mg/kg, both S ‐ and R ‐carvedilol showed a non‐linear pharmacokinetic pattern in control and L‐NAME treated rats, mainly as a consequence of an increased Vd ss .…”
Section: Discussionmentioning
confidence: 99%